SHEAR WAVE STATICS USING RECEIVER FUNCTIONS - van Manen D.; Robertsson J.O.A.; Curtis A.; Ferber R.; Paulssen H. (My University, 2003)
We extend the seismological receiver function method to the exploration seismic domain to solve the problem of shear wave statics for multicomponent data. The method relies on cross-correlation or deconvolution of pressure with radial component traces in the common-receiver domain followed by a stacking step. This procedure is repeated for each receiver, resulting in a profile of high-resolution stacked receiver functions; events corresponding to shallow mode-converted waves constrain the shear wave static. The method is applied to a line of commercial multicomponent seabed seismic data and gives results in good agreement with a conventional statics method, although results along some other lines require additional interpretation. In contrast to seismological receiver function analysis, the main converted wave energy in the receiver functions originates from reflection at shallow interfaces rather than conversion of upgoing wavefields.
Keywords: DECONVOLUTION; EXPLOSION SEISMOLOGY; RECEIVER FUNCTIONS; STATICS; S WAVES